2013
DOI: 10.1017/s1751731113001493
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rearing density on growth, size heterogeneity and inter-individual variation of feed intake in monosex male Nile tilapia Oreochromis niloticus L.

Abstract: The growth dispersion of farmed fish is a subject of increasing interest and one of the most important factors in stocking density. On a duration of 60 days, the effect of stocking density on the growth, coefficient of variation and inter-individual variation of feed intake (CVFI) of juvenile Nile tilapia Oreochromis niloticus L. (14.9 ± 1.2 g) were studied in an experimental tank-based flow-through system. Groups of fish were stocked at four stocking densities: 200, 400, 600 and 800 fish/m3, corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Regarding the selection process, the results coincide with the reports by Azaza et al (2013), and Khaw et al (2016), in which the organisms with less dispersion contributes to obtaining more significant economic benefits. A common practice in aquaculture is to repeatedly select organisms during culture to reduce size variation during growth.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the selection process, the results coincide with the reports by Azaza et al (2013), and Khaw et al (2016), in which the organisms with less dispersion contributes to obtaining more significant economic benefits. A common practice in aquaculture is to repeatedly select organisms during culture to reduce size variation during growth.…”
Section: Discussionsupporting
confidence: 85%
“…This parameter (SGR) decreased with increasing density which was 1.71 ± 0.02 to 0.56 ± 0.02. Azaza et al (2013) also reported that SGR is affected significantly by stocking density and they observed highest SGR for lowest stocking density for Nile tilapia (Oreochromis niloticus). FCR increased with increasing stocking density and the range of FCR was 1.85 ± 0.02 to 2.56 ± 0.11 (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, relatively high rearing density hampers fish health and welfare as well as their production due to stress, predation and competition for food, so the determination of optimal rearing density is a precondition for maximum growth for highest production that leads to maximum profit. Therefore, the impact of rearing density on growth and reproduction of some fish species has been recorded like Atlantic salmon Salmo salar (Hosfeld et al 2009), rainbow trout Oncorhynchus mykiss (McKenzie et al 2012), Nile tilapia Oreochromis niloticus (Azaza et al 2013) and Japanese Medaka Oryzias latipes (Rosemore and Welsh 2012). An interesting work was carried out by Castranova et al (2011) who worked on zebrafish and suggested that using densities as high as 12 fish/liter does not have a negative effect on reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…A critical problem in the production of Nile tilapia Oreochromis niloticus in intensive and hyper-intensive systems (30-400 fish m -3 ) is the heterogeneity of body size. The organisms in the same cohort show different growth rates in response to biotic and abiotic factors (Barbosa et al, 2006;Azaza et al, 2013).…”
Section: Introductionmentioning
confidence: 99%